Предмет: Алгебра,
автор: excellentstart
Решить уравнение: 3(х-1) в степени 2 -(2х-1)(2х+1)=(2х-1) в степень 2
Ответы
Автор ответа:
0
3.(x-1)ˇ2 - (2x-1)(2x+1)=(2x-1)ˇ2
3.(xˇ2-2x+1)-(4xˇ2-1)=4xˇ2-4x+1
3xˇ2-6x+3-4xˇ2+1=4xˇ2-4x+1
-xˇ2-6x+4=4xˇ2-4x+1
5xˇ2+2x-3=0, D=4+60=64,VD=V(64)=8
x1=1/10(-2+8)=1/10.6 =6/10=3/5
x2=1/10(-2-8)=1/10.(-10)=-10/10=-1
3.(xˇ2-2x+1)-(4xˇ2-1)=4xˇ2-4x+1
3xˇ2-6x+3-4xˇ2+1=4xˇ2-4x+1
-xˇ2-6x+4=4xˇ2-4x+1
5xˇ2+2x-3=0, D=4+60=64,VD=V(64)=8
x1=1/10(-2+8)=1/10.6 =6/10=3/5
x2=1/10(-2-8)=1/10.(-10)=-10/10=-1
Автор ответа:
0
как благодраить я тебе все балы отдам
Автор ответа:
0
Ей братишка
Похожие вопросы
Предмет: Алгебра,
автор: evysq32
Предмет: Русский язык,
автор: dddddddddd44
Предмет: Литература,
автор: daniilzhilenkov1
Предмет: История,
автор: alex20062011